2021
DOI: 10.25259/jassm_3_2021
|View full text |Cite
|
Sign up to set email alerts
|

The Posterior Cruciate Ligament: Anatomy, Biomechanics, and Double-Bundle Reconstruction

Abstract: The posterior cruciate ligament (PCL) is the largest intra-articular ligament in the knee and is the primary stabilizer to posterior tibial translation. Historically, the PCL’s functional dynamics and appropriate management after injury have been controversial. However, recent biomechanical and anatomic studies have elucidated a better understanding of PCL function, which has led to development of more anatomic reconstruction techniques. The larger anterolateral bundle and the smaller posteromedial bundle of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 93 publications
0
6
0
Order By: Relevance
“…Kennedy et al 23 reported that the PMB provided the majority of rotational control at increased degrees of knee flexion, which supports the improved relative rotatory stability observed in the DB group when the knee was flexed for our study. 27 Last, there was no significant difference between the techniques when addressing varus laxity. The PCL's role in resisting varus laxity is less pronounced in the intact knee than its role in rotatory and translational stability.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Kennedy et al 23 reported that the PMB provided the majority of rotational control at increased degrees of knee flexion, which supports the improved relative rotatory stability observed in the DB group when the knee was flexed for our study. 27 Last, there was no significant difference between the techniques when addressing varus laxity. The PCL's role in resisting varus laxity is less pronounced in the intact knee than its role in rotatory and translational stability.…”
Section: Discussionmentioning
confidence: 94%
“…The primary biomechanical function of the PCL is to stabilize the knee joint by resisting posterior tibial translation at all flexion angles and limit rotatory instability at higher degrees of knee flexion. 27 Multiple studies have shown that isolated PCL ruptures have the greatest effect at 90° of knee flexion, suggesting that it is most important to clinically assess PCL integrity at 90° of knee flexion. 13,14,32 This is consistent with the results in this investigation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Injury to the posterior cruciate ligament, which acts as the ligament connecting the femur to the tibia, may be related not only to the anatomical morphological parameters of a single structure, but also to the combination of the distal femur and the proximal tibia [23,24] . A full understanding of the in uence of the morphology and correlation between the distal femur and the proximal tibia on PCL is of great signi cance for guiding the treatment and postoperative rehabilitation exercise of patients, but such studies are lacking in clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…However, up to 95% of cases of the PCL tears involve multiligamentous injuries, usually caused by vehicle or sports accidents. 3 , 4 The necessity of a multifactorial approach make the PCL tears challenging to treat and always require an individual approach. When the decision about surgery is made, one should remember that the PCL reconstruction itself is a technically demanding procedure.…”
Section: Introductionmentioning
confidence: 99%